AUDIO DESCRIPTION AND DIVERSITY AWARENESS: FLUTUA MUSIC VIDEO - Villela, Lucinéa Marcelino [UNESP]; Iturregui-gallardo, Gonzalo (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2020)
Brazil has the highest murder rate of transgender people in the world. The paper will focus on a debate of how audio description of some audiovisual products should be used to call the attention to the discrimination and violence suffered by homosexual couples. We have chosen a Brazilian music video called Flutua produced and performed by Johnny Hooker with special participation of the Brazilian singer Liniker, a black trans woman. The clip presents an outstanding visual narrative involving contemporary themes such as gays with disability, gender-fluid and homophobia. During the video a gay deaf couple spends a day having fun with friends in an urban scenario composed by known streets and places of Sao Paulo capital. At the end of the day a member of the group suffered a very violent attack. The audio description of the most relevant scenes, the identities and outfit of the singers, and their movements will be presented having in mind the music as protagonist of Flutua.

O Brasil tem o maior índice de pessoas transgêneras do mundo. O artigo focará no debate sobre como a audiodescrição de alguns produtos audiovisuais deve ser usada para chamar a atenção para a discriminação e para a violência sofrida pelos casais homossexuais. Escolhemos o videoclipe Flutua, produzido e interpretado por Johnny Hooker com uma participação especial da cantora brasileira Liniker, uma mulher trans negra. O clipe apresenta uma narrativa visual excepcional envolvendo temas contemporâneos tais como gays com deficiências, gênero fluido e homofobia. Ao longo do vídeo, um casal gay surdo passa um dia se divertindo com amigos em um cenário urbano composto por ruas conhecidas da cidade de São Paulo. No final do dia, um membro do grupo sofre um ataque muito violento. Serão apresentadas as audiodescrições das cenas mais relevantes, das identidades e do figurino dos cantores e seus movimentos sempre colocando a música como protagonista de Flutua.
AUDIODESCRIÇÃO E CONSCIÊNCIA DA DIVERSIDADE: VIDEOCLIPE FLUTUA
Keywords: audio description; accessible audiovisual translation; diversity awareness; audiodescrição; consciência da diversidade; tradução audiovisual acessível